Bone injection gun placement of intraosseous needles. Issue 5 (20th April 2005) - Curran, Andrew; Sen, Ayan
Abstract : A short cut review was carried out to establish whether the Bone Injection Gun is better than a standard intraosseous (IO) needle at obtaining IO access. A total of 129 papers were found using the reported search, of which three represent the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.